Pemberdayaan Mantan Penderita Gangguan Jiwa - Rahman, Euis Septia; Krishendrijanto, . (University of Jember)
This research was intended to identify the empowerment process of ex-mental disorder sufferers conducted by Metal Islamic boarding school, Rejoso Village, District of Rejoso, Pasuruan Regency. Considering that the ones who would be empowered were abnornal individuals who needed special care and later special treatment. The fact that the institution carrying out the empowerment was a conventional institution was indeed what made the researcher interested in studying it. How was the empowerment process of ex-mental disorder sufferers conducted by Metal Islamic boarding school Pasuruan to help them to become individual figures that could recreate their social functions, so that they could become independent individuals who could meet their needs and live in prosperity? This research used qualitative approach, with case study research design. In data collection, researchers used several techniques of observation including: passive participatory observation, straight and hidden observation, the interview used was unstructured interview, and documentation. The research results were that: the empowerment process of ex-mental disorder sufferers conducted by Metal Islamic boarding Pasuruan passed through the stages of empowerment as follows: (i) the pre-empowerment (inspection, healing), (ii) the empowerment phase (recovery, social functioning, service delivery), (iii) the termination phase (repatriation, getting married). Keywords: empowerment, ex-mental disorder sufferers, Metal Islamic Boarding School Pasuruan.